2015
DOI: 10.4236/detection.2015.34004
|View full text |Cite
|
Sign up to set email alerts
|

Radium and Uranium Concentrations Measurements in Vegetables Samples of Iraq

Abstract: In the present study twenty-two vegetable samples were collected from Iraqi market. Sealed can technique using CR-39 plastic track detector strippable has been used in order to measure radium and uranium concentrations. Etching was done with 6.25 N NaOH and optical microscope was used with the purpose of counting of alpha particle tracks. The values of effective radium content are found to range from 0.074 Bq/ kg to 0.566 Bq/ kg with the mean value of 0.317 Bq/kg. The values of uranium concentrations are found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The levels of uranium concentrations in all studied food crops were lower than the allowed limits for public (1.7 ppm) given by (UNSCEAR) (22,32) . The values of radium content in various types of foodstuffs of other countries are different and as summarised in table 4.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The levels of uranium concentrations in all studied food crops were lower than the allowed limits for public (1.7 ppm) given by (UNSCEAR) (22,32) . The values of radium content in various types of foodstuffs of other countries are different and as summarised in table 4.…”
Section: Discussionmentioning
confidence: 57%
“…As mentioned in (table 3) the levels of UC, RC and RER were the highest in the root vegetables, which included carrot, onion, potato, radish and turnip than another types of leafy vegetables and fruit. This finding is due to the transfer factors of the radioactive materials from the soil to the plant as well as the difference in the nature of the plant (22,31) .…”
Section: Discussionmentioning
confidence: 99%
“…Based on highlights of the study Hakonson-Hayes et al [92], Giri et al [93] and Hashim & Najam [94], it was found that the main way people are exposed to U toxicological and radiological ill-effects is by directly drinking contaminated groundwater, accounting for more than 85-99% of the health risks for human consumers. Considering established safety measures and relying on oral ingestion, the World Health Organization (WHO) has set a Tolerable Daily Intake (TDI) of 0.6 µg/kg body weight per day for soluble U [95].…”
Section: Occurrence Of Uranium In Soil-plant Systemmentioning
confidence: 99%
“…Radon concentrations C Rn (Bq m −3 ), effective radium content C Ra (Bq kg −1 ), uranium concentration C U (ppm) and exhalation rates in the study area were calculated using equations given in references [7,8,9,10]. Calibration factor CF is calculated using the formula given in reference [11], the calculated value of CF is equal to 0.04891 Track cm -2 d -1 /Bqm -3 .…”
Section: Calculationmentioning
confidence: 99%